Parasitosis in appendectomy cases - Karaman, Ülkü; Türkmen, Emine; Iraz, Meryem; Karataş, Turgay; Çolak, Cemil (TIP ARASTIRMALARI DERNEGI, 2010)
Aim: Obstruction of lumen of appendix vermiformis causes inflammation and requires surgery. The study aimed to detect any parasitosis in appendiceal specimens brought to pathology laboratory. Method: A total 916 appendectomy specimens from Faculty of Medicine at Inonu University between 2002 and 2005 were examined for inflammation and luminal parasitosis. Result: Adult worms and eggs of Enterobius vermicularis were detected in 23 (2.5%) of all cases, while Taenia spp. were found in only 2 (0.2%) cases. Also parasites were found in 8 of (2.0%) of 391 construction appendicitis, and in 5 (1.3%) of 384 acute appendicitis cases. Moreover, plasma cells and polymorphonuclear leukocytes were observed, respectively, in 18, and 2 of Appendix vermiformis cases with parasite. Eosinophils in lamina propria were detected in all cases. Conclusion: Therefore, the intestinal parasitosis should be considered in the differential diagnoses of appendicitis. Education on how to prevent parasitosis should be included in training programs to avoid any unnecessary surgery.
Apendektomi olgularında parazitoz
Keywords: Appendectomy specimen; Inflammation; Intestinal parasite; Surgery